Legal Protection of the Rights of the Defendant in Criminal Trials through Electronic Media - Ida Bagus Anggapurana Pidada (Nurani Hukum, 2021)
The Covid19 pandemic also affected the law enforcement process in Indonesia, including the law enforcement process in court. In the online trial, the problem is how the position / existence of the judge who should be able to control the trial process who is not in the same room as the defendant. It is feared that the existence of this difference in location will result in the weakening of the judge's decision making to be able to dig deeply the hidden truths in a case. Operational constraints in the availability of an internet connection also have the potential to become a problem in the implementation of criminal proceedings. Trials with electronic media are one of the modern legal solutions that cannot be avoided along with the advancement of the digital world and globalization. Even so, the rights of the defendant in the trial using electronic media must also be guaranteed protection for the sake of upholding justice in the law. This type of research is normative juridical legal research. The normative juridical approach is a research that examines the study of documents, namely using various secondary data such as statutory regulations, court decisions, legal theory, and it can be in the form of the opinions of scholars. Legal protection for the defendant in a trial using electronic media is regulated in the Supreme Court Regulation No. 4 of 2020 concerning Electronic Administration and Trial of Criminal Cases in Courts. Legal protection for the rights of the defendant has been regulated in Law Number 8 of 1981 concerning Criminal Procedure Law in articles 50 to Article 68. In addition, legal protection for the rights of the accused as stipulated in the Universal Declaration of Human Rights (DUHAM) also applies. .